2000
DOI: 10.21273/jashs.125.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Nitrogen Concentration in Hydroponic Solutions Affects Onion Flavor and Bulb Quality

Abstract: To test the effects of high nitrogen (N) fertilization levels on onion quality and bulb flavor, `Granex 33' onions (Allium cepa L.) were greenhouse grown in hydroponic solution culture with increasing N concentrations. Nitrogen was adjusted in the solutions with NH4NO3 and increased incrementally from 0.22 g·L-1 to 0.97 g·L-1 over five treatments. Plants were harvested at maturity and subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
2
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 19 publications
(29 reference statements)
8
70
2
4
Order By: Relevance
“…Total ACSO concentration has previously been reported to be influenced by very high N fertility levels. 15 N fertility also influenced the concentration of MCSO in the bulb (P ≤ 0.001; Fig 4(A)). Average bulb concentrations of MCSO ranged from 0.48 to 4.32 mg g −1 FW.…”
Section: Precursor and Peptide Intermediatesmentioning
confidence: 95%
See 3 more Smart Citations
“…Total ACSO concentration has previously been reported to be influenced by very high N fertility levels. 15 N fertility also influenced the concentration of MCSO in the bulb (P ≤ 0.001; Fig 4(A)). Average bulb concentrations of MCSO ranged from 0.48 to 4.32 mg g −1 FW.…”
Section: Precursor and Peptide Intermediatesmentioning
confidence: 95%
“…These values are similar to those reported for 'Granex 33' onions grown with high N and similar S fertility levels. 15 Because SO 4 2− is generally stored in the vacuole and is unable to contribute immediately to the production of flavour compounds in onion, it is important to determine the amount of total S that is contributed by SO 4 2− . By knowing total S and SO 4 2− -S, the amount of S that is bound organically (organic-S) in the bulb can be estimated.…”
Section: Total Bulb Sulphur and Sulphatementioning
confidence: 99%
See 2 more Smart Citations
“…Glasshouse studies have demonstrated that sulfate supply is the major environmental factor determining pungency (Randle, 1992;Randle and Bussard, 1993) and therefore mild onion production is conducted on light soils where S fertility can be readily controlled. In addition, hydroponic studies have also shown that nitrogen supply can affect flavour precursor levels (Coolong and Randle, 2003;Randle, 2000). However, surprisingly few field-based studies have demonstrated effects of S (or N) nutrition on pungency (Bakr and Gawish, 1998;Kumar and Sahay, 1954).…”
Section: Introductionmentioning
confidence: 99%